TEACHING PRACTICAL THEATRICAL 3D PRINTING creating props for production. - Berls, Robert C. ([S.l.] : FOCAL PRESS, 2024)
Teaching Practical Theatrical 3D Printing: Creating Props for Production is a cohesive and practical guide for instructors teaching 3D printing techniques in stagecraft, costume and props courses. Written for the instructor, this book uses non-technical language to explain 3D printers, their workflows and products. Coverage includes the ins and outs of multiple filaments, pros and cons of different types of printers, shop or laboratory setup and safety concerns. The book features lesson plans, rubrics and class-tested sample student projects from design to finished product that highlight learning objectives and methodologies, as well as software and hardware usage explanations and common problems that can occur within design and printing. Step-by-step instructions are included for many types of projects, including fake noses, candlestick phones, buttons, 3D scans, historical recreations and linear actuators. The book also contains examples of poor, average and excellent work with grading explanations and guidance on how to help the student move to the next level with their projects. Chapter objectives, chapter summaries, checklists and reflection points facilitate an instructor in gaining confidence with 3D printers and incorporating their use in the classroom. Teaching Practical Theatrical 3D Printing is an excellent resource for instructors of Props and Costume Design and Construction courses that are interested in using state of the art tools and technology for theatre production. Fully editable files for every object featured in the book are available at www.routledge.com/9781032453279, allowing readers to jump-start their projects and giving them the flexibility to change and redesign the items to best fit their needs.
Keywords: Stage props -- Design and construction -- Study and teaching; Stage props -- Computer-aided design -- Study and teaching; Three-dimensional printing -- Study and teaching; PERFORMING ARTS / Theater / Stagecraft; EDUCATION / Teaching Methods & Materials / Arts & Humanities